Optimasi Setting Parameter Electrical Discharge Maschining (Edm) Sinking Terhadap Kekasaran Permukaan dan Waktu Pengerjaan Material Skd-11 dengan Metode Taguchi-Grey Relational Analysis - Risma Aris Maya; Bayu Wiro K.; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
Abstract – Electrical Discharge Machining (EDM) Sinking is one type of EDM that is widely used inmaking molds and making dies. There are several factors that can determine the quality of a product,expecially in making dies/dies including surface roughness and processing time. Getting a smallsurface roughness with efficient working time it easily obtained if the machine operator knows theexact parameters when machining is done. The parameters used are gap voltage, on time, and offtime by conducting 27 experiments. The method used is Taguchi-Grey Relational Analysis. Theresults of this study were obtained by the optimum parameter combination consisting of gap voltageworth 30 volts, on time 120 s and off time 20 s with a contibution percentage of gap voltage 42,475%, on time 34,778 % and off time 17,536 %